1994
DOI: 10.4319/lo.1994.39.6.1411
|View full text |Cite
|
Sign up to set email alerts
|

Potentials of photolytic rhodamine WT as a large-scale water tracer assessed in a long-term experiment in the Loosdrecht lakes

Abstract: The dispersal of 0.13 kg of water-tracer rhodamine WT in the Loosdrecht lakes was surveyed during 19 months. Solid-phase extraction and liquid chromatography were used to measure the very low concentrations of rhodamine WT in the experiment. The detection limit was -2 x lo-l1 kg m-3. The photolysis constant of rhodamine WT was measured in a laboratory experiment. A numerical model for hindcasting the dilution of a photolytic tracer in the lake system was developed. Model results compare well with observations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 16 publications
0
23
1
Order By: Relevance
“…The potential for turbidity to impact upon our field study was assessed by measuring a range of RWT solutions prepared using water from our field site, and no significant deviation from expected fluorescence was observed hence any possible effects of turbulence on RWT fluorescence measurements were ignored for the remainder of the study. A number of studies have also demonstrated that the use of RWT in quantitative studies may be compromised by photochemical decay of RWT over time (Smart and Laidlaw, 1977;Tai and Rathbun, 1988;Suijlen and Buyse, 1994;Upstill-Godard et al, 2001;Dierburg and C. H. Mines et al: Use of rhodamine WT as proxy for point source pollutants DeBusk, 2005) and loss of RWT due to adsorption (Smart and Laidlaw, 1977;Wilson et al, 1986;Sabatini and Austin, 1991;Shiau et al, 1993;Di Fazio and Vurro, 1994;Soerens et al, 1994;Kasnavia et al, 1999;Close et al, 2002;Keefe et al, 2004;Kung et al, 2000;Vasudevan et al, 2001;Lin et al, 2003;Pang et al, 2003;Richardson et al, 2004;Dierburg and DeBusk, 2005) but as the work described here focused on the use of RWT within a closed pipe surface water drainage network these potential losses were deemed insignificant and not re-examined. Given this range of potential compromising factors, the inconsistent nature of field results concerning RWT fate and transport (Tai and Rathbun, 1988;Jones and Jung, 1990;Suijlen and Buyse, 1994;Ptak and Schmid, 1996;Kung et al, 2000;Upstill-Godard et al, 2001;Close et al, 2002;Lin et al, 2003) is unsurprising.…”
Section: Introductionmentioning
confidence: 99%
“…The potential for turbidity to impact upon our field study was assessed by measuring a range of RWT solutions prepared using water from our field site, and no significant deviation from expected fluorescence was observed hence any possible effects of turbulence on RWT fluorescence measurements were ignored for the remainder of the study. A number of studies have also demonstrated that the use of RWT in quantitative studies may be compromised by photochemical decay of RWT over time (Smart and Laidlaw, 1977;Tai and Rathbun, 1988;Suijlen and Buyse, 1994;Upstill-Godard et al, 2001;Dierburg and C. H. Mines et al: Use of rhodamine WT as proxy for point source pollutants DeBusk, 2005) and loss of RWT due to adsorption (Smart and Laidlaw, 1977;Wilson et al, 1986;Sabatini and Austin, 1991;Shiau et al, 1993;Di Fazio and Vurro, 1994;Soerens et al, 1994;Kasnavia et al, 1999;Close et al, 2002;Keefe et al, 2004;Kung et al, 2000;Vasudevan et al, 2001;Lin et al, 2003;Pang et al, 2003;Richardson et al, 2004;Dierburg and DeBusk, 2005) but as the work described here focused on the use of RWT within a closed pipe surface water drainage network these potential losses were deemed insignificant and not re-examined. Given this range of potential compromising factors, the inconsistent nature of field results concerning RWT fate and transport (Tai and Rathbun, 1988;Jones and Jung, 1990;Suijlen and Buyse, 1994;Ptak and Schmid, 1996;Kung et al, 2000;Upstill-Godard et al, 2001;Close et al, 2002;Lin et al, 2003) is unsurprising.…”
Section: Introductionmentioning
confidence: 99%
“…Distilled water blank values never exceeded these thresholds. Although such detection limits were fully acceptable for our current purpose, much lower thresholds are routinely possible in other applications of this technique (Suijlen et al 1994). …”
Section: Methodsmentioning
confidence: 94%
“…For rhodamine analysis, we used a slightly modified version of the procedure described by Suijlen et al (1994). Full details of the modified method are given elsewhere (Den Das et al 1997).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations